Growth temperature determines titanium dioxide nanoparticles response by Saccharomyces cerevisiae UE-ME3. - Capela-Pires, JM (2012)
The environmental levels of titanium dioxide nanoparticles (TiO2-NP), a new material described as ROS generator, has increased in several regions of the earth due its massive industrial use. Thus, the main purpose of this work was to determine the influence of temperature on response to TiO2-NP by S. cerevisiae UE-ME3.The results show that cells grown at 28 ºC show dry weight, protein and glutathione contents higher than cells grown at 40 ºC. In addition GSH content increased in cells exposed to nanoparticles at 28 ºC. The GSH/GSSG ratio is greater in cells grown at 40°C, probably due a sharp decrease of GSSG and GPx activity, more evident in TiO2-NP exposed cells. Furthermore, an increase of MDA level detected in S. cerevisiae growing in presence of 1µg/mL TiO2-NP at 28 ºC, related with an increase of LOX and GPx activities as well as ROS contents, points TiO2-NP as inducer of oxidative stress and cell death.